1970
DOI: 10.1210/endo-86-6-1410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porcine Beta Melanocyte-Stimulating Hormone on Blood Lymphocyte Count and Serum Corticosterone Concentration of the Rabbit

Abstract: Beta MSH is known to lack lipolytic or corticotropic activity in the rat. In intact rabbits, the injection of 10-100 ng purified porcine /3-MSH not only elevated serum free fatty acid (FFA) concentration 2 hr later, but also caused a reduction in blood lymphocyte count and a marked increase in serum corticosterone concentration. The effects of 10 and 100 ng (8-MSH on blood lymphocytes, serum FFA and serum corticosterone were similar in magnitude to those produced by 10 and 100 tig oxycellulose-purified ACTH. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, Kastin, Miller, González-Barcena, Hawley, Dyster-Aas, Schally, Velasco de Parra & Velasco (1971) reported that the levels of plasma cortisol remained normal after the infusion of MSH in human subjects. In experimental animals the situation is similarly confused (see Karkun, Kar & Sen, 1963), although Rudman, Del Rio, Bixler & Barnett (1970) have since demonstrated that purified /?-MSH exhibits corticotrophic activity, equal to that of ACTH, when administered to rabbits.…”
Section: Endocrine Controlmentioning
confidence: 99%
“…However, Kastin, Miller, González-Barcena, Hawley, Dyster-Aas, Schally, Velasco de Parra & Velasco (1971) reported that the levels of plasma cortisol remained normal after the infusion of MSH in human subjects. In experimental animals the situation is similarly confused (see Karkun, Kar & Sen, 1963), although Rudman, Del Rio, Bixler & Barnett (1970) have since demonstrated that purified /?-MSH exhibits corticotrophic activity, equal to that of ACTH, when administered to rabbits.…”
Section: Endocrine Controlmentioning
confidence: 99%
“…As anencephalic infants had low growth hormone levels and stimulation of growth hormone production was unsuccessful with a single exception (Grumbach and Kaplan, 1973) anti because high levels of prolactin have been detected in anencephaly (Robijn, 1973), we believe that growth hormone, or MSH, is likely to be the principal additional adrenotropic factor. This hypothesis is supported by animal experiments (Lostroh, 1958;Rudman et al, 1970;Colby et a l , 1973;Piva et al, 1973).…”
Section: Discussionmentioning
confidence: 80%